2004
DOI: 10.1167/iovs.03-1064
|View full text |Cite
|
Sign up to set email alerts
|

Insulin, Not Leptin, Promotes In Vitro Cell Migration to Heal Monolayer Wounds in Human Corneal Epithelium

Abstract: Exposure of corneal epithelium to insulin facilitated closure of in vitro small wounds through enhanced cell migration instead of proliferation, which depended on ERK 1/2 and PI3-kinase signaling. These data suggest a mechanism by which insulin may influence corneal wound healing in vitro. In vivo, disruptions to the insulin signaling pathway observed in diseases such as diabetes might account for the delayed wound healing and corneal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 51 publications
1
53
0
5
Order By: Relevance
“…Insulin has been shown to enhance corneal epithelial cell migration and to aid in the closure of small wounds in vitro. 11 In animal studies involving diabetic rats, insulin application either topically or subcutaneously helped in healing corneal EDs. Zagon et al 12 demonstrated that 32 hours after 5-mm diameter circular corneal abrasion is induced in rats, the percent ED was 67% greater in insulinuntreated diabetic rats than in subcutaneous insulin-treated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin has been shown to enhance corneal epithelial cell migration and to aid in the closure of small wounds in vitro. 11 In animal studies involving diabetic rats, insulin application either topically or subcutaneously helped in healing corneal EDs. Zagon et al 12 demonstrated that 32 hours after 5-mm diameter circular corneal abrasion is induced in rats, the percent ED was 67% greater in insulinuntreated diabetic rats than in subcutaneous insulin-treated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Insulin has been shown to enhance corneal epithelial cell migration and aid in closure of small wounds in vitro and in animal studies. [11][12][13] In this study, we evaluated and compared the abilities of Optisol GS and Life 4°C to preserve the epithelium of corneal donor tissue during storage.…”
mentioning
confidence: 99%
“…More recently, Woost and colleagues 23 have reported an increase in the tensile strength of wounds in healthy rabbits with full-thickness, perforating, corneal incisions following 3 daily applications of insulin. Shanley and coworkers 24 documented an increase in cell migration using an in vitro model of an immortalized simian virus 40 human corneal epithelial cell line treated with insulin. Thus, to our knowledge, this is the first study showing that the topical ocular route of insulin can modulate wound healing of the cornea in diabetic animals.…”
Section: Commentmentioning
confidence: 99%
“…Surveying the vast literature on the scratch-wound assay for both epithelial and non-epithelial cells, two generalizations can be made: (1) after a short (2-4 hours) refractory period following wounding, rectangular wounds close at a steady rate (Nishio et al, 2005;Pullar et al, 2006;Richards et al, 2004;Shanley et al, 2004;Takeda et al, 2004); and (2) cell division increases in response to wounding (Todaro et al, 1965), but does not affect closure rates (Block et al, 2004;Farooqui and Fenteany, 2005;Sponsel et al, 1994). Grown in simulated culture to confluence and then 'wounded' by deleting a strip of cells, populations of our agents reproduce these characteristics of collective cell migration, as well as other qualitative behaviors we observe for L1 cells.…”
Section: Introductionmentioning
confidence: 99%